Segregation in carbon steels - Liong, Wei Hao. (2009)
In the shipping industry, carbon steel is widely used to build ship decks and oil rigs. Carbon steel is able to withstand heavy load but due to the segregation problem, it causes delamination. Cracks can be easily initiated and propagated along regions with high level of segregation. Segregation is a manufacturing problem that is very difficult to avoid. It is caused by the non-uniformity of chemical composition within metals and alloys during solidification. From a commercial point of view, when segregation centerline (high level of segregation at center region) is detected, it will be costly to replace the whole component. Therefore heat treatment process will be carried out on the carbon steel to eliminate the segregation problem. The author hopes the information will aid the metallurgists and engineers when performing heat treatment on carbon steel.